ANALISIS EKUITAS MEREK GULA PASIR GULAKU DAN GUPALAS - Darul Bakhtiar (Jurnal Ekonomi dan Bisnis Airlangga, 2017)
Introduction: This study aims to study the various elements of brand equity (brand equity) granulated sugar products, such as: brand awareness, brand association, brandperceived quality, and brand loyalty by comparing two brands of sugar products are Gulaku and Gupalas. Gulaku as first mover advantages which the first player to enter a particular industry is often considered to have the first opportunity to build market share since 2002, while Gupalas is a product that has just appeared in 2011.Methods: The sampling method used is purposive sampling with the number of respondents who were taken as the sample in the study of100 people consumers of sugar, especially housewives who are in theMadiun area. Analyzer used in this research is the analysis of the meandifference test through t test and a confirmation through Manova test.Results: Brand equity research results indicate that Gulaku have higherbrand equity than Gupalas. The difference was due to the three elements of brand equity include brand awareness, brand associations and brandloyalty of Gulaku much higher than Gupalas. While Gupalas Gulaku only be offset in terms of perceived quality alone.Conclusion and suggestion: This study is used as input Gupalasmanufacturers namely PT. Nusantara Plantation XI as brand equityevaluation of Gupalas include brand equity, which is supposed to be improved.